Telaah Literatur Tentang Faktor-Faktor yang Mempengaruhi Konservatisme Akuntansi - Lia Alfiah Dinanar Hati (Jurnal Ekonomi dan Pendidikan, 2011)
This paper examine several factor that impact to accounting conservatism practice. Conservatism is commonly defined as the differential verifiability required for recognition of profits versus losses. Regardless of the different opinion about role of accounting conservatism, in fact, this principle is still in uses until now and be one of the dominant principle in accounting. Through this article the author do review of several previous studies about accounting conservatism at Indonesia and other country. From several review we conclude that accounting conservatism is affected by factors of contracting, litigation risk, political costs, regulations, financial distress and conflict of interest between shareholders and bondholders.